How Does Host Carbon Concentration Modulate the Lifestyle of Postharvest Pathogens during Colonization? - Prusky, Dov B.; Bi, Fangcheng; Moral, Juan; Barad, Shiri (Frontiers in Plant Science, 2016)
Postharvest pathogens can penetrate fruit by breaching the cuticle or directly through wounds, remain quiescent and they show disease symptoms only long after infection. During ripening and senescence, the fruit undergo physiological processes accompanied by a decline in antifungal compounds, which allows the pathogen to activate a mechanism of secretion of small effector molecules that modulate host environmental pH. This results in the transcript activation of fungal genes under their optimal pH conditions, enabling the fungus to use a specific group of pathogenicity factors at each particular pH. New research suggests that carbon availability in the environment of the activating pathogen is a key factor triggering the production and secretion of small pH-modulating molecules: ammonia and organic acid. Ammonia is secreted under limited carbon and gluconic acid under excess carbon. This mini review describes our most recent knowledge on the mechanism of activation of the biosynthesis and secretion of fungal molecules that modulate the host pH, and their contribution to the transition from quiescence to necrotrophic lifestyle by the postharvest pathogens.